2016
DOI: 10.4269/ajtmh.16-0419
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Pain and Expectations for Its Treatment Among Former Buruli Ulcer Patients

Abstract: Abstract. Buruli ulcer (BU) is one of the 17 neglected tropical diseases for which the World Health Organization has adopted resolutions to improve treatment. BU was previously described as a relatively painless condition; however, recent research has indicated that some patients experience substantial pain. The objective of this study was to explore patients' experiences of pain and their expectations for its treatment. Semistructured interviews were conducted in a BU-endemic region of Ghana. Interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Examples include: (i), in China, the actions of antibiotics and nonsteroidal anti‐inflammatory drugs are often conflated, as Xiaoyanyao , drugs that can eliminate inflammation, [ 77–80 ] leading to antibiotic use for conditions with self‐limited inflammation; (ii), in Nigeria, women are increasingly using antibiotics to reduce menstrual problems (cramps, heavy flow, headaches, pimples/acne, moodiness, tender breasts, backache, joint and muscle pain) and to prevent “infections” from feminine sanitary products [ 81,82 ] ; (iii), in Thailand, tetracycline is commonly used for women's “uterus” complaints, termed moot luuk , manifesting as vaginal discharge and pelvic pain [ 83,84 ] ; and (iv), a common (world‐wide) practice is self‐treatment of wounds with crushed antibiotic capsules to dry them, reduce pain, and treat infection. [ 76,85–89 ]…”
Section: Factors Driving Variation In Antibiotic Use and Overusementioning
confidence: 99%
“…Examples include: (i), in China, the actions of antibiotics and nonsteroidal anti‐inflammatory drugs are often conflated, as Xiaoyanyao , drugs that can eliminate inflammation, [ 77–80 ] leading to antibiotic use for conditions with self‐limited inflammation; (ii), in Nigeria, women are increasingly using antibiotics to reduce menstrual problems (cramps, heavy flow, headaches, pimples/acne, moodiness, tender breasts, backache, joint and muscle pain) and to prevent “infections” from feminine sanitary products [ 81,82 ] ; (iii), in Thailand, tetracycline is commonly used for women's “uterus” complaints, termed moot luuk , manifesting as vaginal discharge and pelvic pain [ 83,84 ] ; and (iv), a common (world‐wide) practice is self‐treatment of wounds with crushed antibiotic capsules to dry them, reduce pain, and treat infection. [ 76,85–89 ]…”
Section: Factors Driving Variation In Antibiotic Use and Overusementioning
confidence: 99%
“…Good wound management is required not only for faster and sequelae-free epithelialization of ulcers but also for increased quality of life of patients. BU lesions were previously noticed to be associated with no or limited pain, but recent studies have revealed that many patients actually experience pain after the start of treatment [ 72 , 95 , 96 ]. This pain is most felt during wound dressing change when in many settings, gauze is the only dressing type being used [ 97 ].…”
Section: Importance Of Wound Management In Buruli Ulcermentioning
confidence: 99%
“…Examination of the 24 studies included in this systematic review identified that five studies were conducted in Nigeria (Alexander et al,2015, Arinze et al, 2018, Igwesi-Chidobe et al, 2017, Olaogun et al, 2008, Suleiman et al, 2016), a further five studies were from Ghana (Aziato et al, 2017, Aziato & Adejumo, 2014, Aziato et al 2016, Aziato et al, 2017, Woolley et al, 2016), four from South Africa (Beck, 2000, Lourens et al, 2020, Nortje & Albertyn, 2015, Ratshikana-Moloko et al, 2020), two from studies were from Ethiopia (Bishaw et al, 2020, Eshete et al, 2019), two from SSA (Clancy, 2014, Harding, 2003), and one study from from Ghana & Benin (de Zeeuw et al, 2015), Rwanda (Johnson et al, 2015), Uganda (Nabukenya et al, 2015), Kenya (Onsongo, 2020), Zimbabwe (Sonquishe & Levy, 1990), and Cameroon (Young et al, 2018).…”
Section: Resultsmentioning
confidence: 99%